The Difference Chlorophyll of Triticum aestivum L. Planted Hydroponic - Rifkha Fadilla; Elsa Yuniarti (Serambi Biologi, 2020)
Triticum aestivum L. which is called wheat grass contains high levels of chlorophyll. Chlorophyll levels are also influenced by the growing media used. The farming method that is in demand is hydroponics. The purpose of this study was to determine differences in chlorophyll levels of Triticum aestivum grown by growmore hydroponics and nutrients and AB Mix. This research is an experimental study that was analyzed by a T-test one sample test at a significant level of 5% carried out in February 2019 at the Biology Research Laboratory, FMIPA UNP. Measuring chlorophyll levels using the Wintermans method with leaf samples as much as 100 g aged 10 days after planting. The results showed that there were differences in the levels of hydroponic planted chlorophyll using growmore and AB Mix where S. (2-tailed) 0.023 <0.05. The highest chlorophyll levels are found in growmore nutrients.